Analisis karakter curiosity dalam pelajaran matematika pada siswa kelas IX SMP - Oktaviani, Michel Febri; Hanifah, Hanifah (IKIP Siliwangi, 2025)
The character of curiosity is inherent to support students in actively exploring an abstract concept such as mathematics. The lack of studies that discuss the importance of curiosity in students, which is the main urgency of the need to conduct this study to provide a reflection that there is a suboptimal character of curiosity itself. Thus, the purpose of this study focuses on describing the character of curiosity shown by analyzing 30 students at one of the Junior High Schools in Karawang Regency when mathematics lessons are taking place. Therefore, a descriptive qualitative approach was used with a simple random sampling technique for grade IX students. In data collection, a non-test instrument was used in the form of a questionnaire containing indicators of curiosity, including 1) Asking, 2) Reading from other sources, 3) Learning initiative 4) Desire to solve problems. The findings show the need for improvement in the character of curiosity because it is shown in one of the indicators of curiosity, namely reading from other sources, showing a percentage of 55%, meaning that only a large part has the desire to explore information from various existing references. Likewise with other indicators, it shows that most students still cannot be said to be optimal from the entire sample used.